(untitled) (Clinics, 2011)
OBJECTIVE: Involvement of the left ventricular anterior wall in ST-elevation myocardial infarction has a worse prognosis compared with other regions. In non-ST-elevation myocardial infarction, noninvasive methods of locating the ischemic myocardial territory have been limited. The objective of this report is therefore to determine what factors are predictive of the anterior location of the ischemic myocardial territory. METHODS: This study included 170 patients with non-ST-elevation myocardial infarction. Clinical, echocardiographic, and laboratory characteristics, including B-type natriuretic peptide measured within 24 hours of hospitalization, and coronary angiographic features were analyzed. RESULTS: The mean age was 64.5 ± 12.3 years, and 112 of the patients were male (66%). The median follow-up was 23 months. The territory involved, as determined from the angiogram, was divided into anterior [n = 80 (47%)] regions and inferior and lateral [n = 90 (53%)] regions. Multivariate analysis showed that B-type natriuretic peptide was the only independent predictor of an anterior wall infarct [OR = 3.70 (95% CI: 1.61 - 8.53); P = 0.002] in non-STelevation myocardial infarction patients. Multivariate analysis also showed that B-type natriuretic peptide was an independent predictor of in-hospital cardiac events during index admission [OR = 5.05 (95% CI: 1.49 - 17.12); P = 0.009] and of cardiac events occurring during follow-up [HR = 1.79 (95% CI: 1.05 - 3.04); P = 0.032]. CONCLUSIONS: B-type natriuretic peptide was the only factor independently associated with anterior wall involvement in non-ST-elevation myocardial infarction, and the peptide levels upon admission predicted in-hospital and subsequent cardiac events.